PELATIHAN PENGGUNAAN MEDIA BERBASIS TEKNOLOGI UNTUK GURU DI KABUPATEN PANGKAJE’NE DAN KEPULAUAN - Sitti Marlina; Putri Athirah Azis, Nova Dwi Pratiwi S, Muh. Anas M (JOURNAL OF COMMUNITY DEDICATION, 2023)
The need to improve the quality of teachers is something that must be done by educational units. SMP Negeri 1 Bungoro Kab. Pangkep took the initiative to improve the skills of teachers, especially in making information technology-based learning media. The goal is to increase the quality of learning processes and outcomes in schools. The community service implementation team was asked to provide assistance in activities to improve the skills of SMP Negeri 1 Bunggoro Regency teachers. Pangkep in terms of making information technology-based learning media. This training program can meet the needs of the community (teachers) within the scope of SMP Negeri 1 Bungoro Kab. Pangkep in order to improve the quality of teachers at SMP Negeri 1 Bungoro Kab. Pangkep, especially in making information technology-based learning media. This training program is also carried out in the context of the success of government programs for teachers so that they are literate in technology and apply it in the learning process which results in the effectiveness of achieving learning objectives.